The study of the level of professional burnout among pharmacists - Bondarieva, I. V.; Malyi, V. V.; Rohulia, O. Yu.; Babicheva, G. S.; Malinina, N. G.; Chehrynets , A. A. (Social Pharmacy in Health Care, 2024)
Aim. To determine the level of professional burnout among pharmacists in different regions of Ukraine and evaluate the main factors contributing to the occurrence of this condition. Materials and methods. During the study, the methods of system analysis, generalization, comparison, logical analysis, as well as the survey method according to Maslach and the developed author’s questionnaire were used. Results. Most pharmaceutical workers experience fatigue, reduced interest in work and difficulty waking up in the morning, which indicates a high level of occupational stress and burnout. In addition, a significant percentage of respondents complain of emotional exhaustion and depression, which deepens the negative impact on their motivation. The main factors contributing to burnout are job monotony, low financial remuneration, workplace conflicts and lack of proper support from colleagues and management. In addition, most pharmaceutical workers feel that their work is underestimated, which reduces overall satisfaction with the profession. The consequences of professional burnout are deterioration in the quality of customer service, an increase in the number of errors in the pharmacists’ work, and an increase in staff turnover in pharmacies. Conclusions. The vast majority of pharmacists experience signs of professional burnout, which often forces them to change their workplace or even their field of activity. In order to reduce this phenomenon, it is necessary to take comprehensive measures aimed at optimizing the workload, providing psychological support, creating favorable working conditions and properly evaluating the professional efforts of pharmaceutical workers. Special attention should be paid to the implementation of programs for the development of professional stress management skills.